Earning Management through Marginal Effect of Firm Based and Regional Economic Indicators: A Study on Listed Firms in Kuwait - Al Hussaini , Ahmed Nahar (Asian Journal of Empirical Research, 2019)
Under the situation of complex business firms, organizations are trying to enhance their earning capacity while competing in the marketplace. The core objective of the present study is to consider the Trading Income Ratio as a core indicator of earning capacity of the business through both firms based and regional economic indicators during the first half of the present decade. For this purpose, size, LR, credit expansion through the provision of loans, BDPS, GDP, and CPI has been considered. The effect of robust regression equations along with fixed and random effect explains that size, LR, and GDP are among the significant predictors for the earning capacity from 2011 to 2015. For the difference between the coefficient of fixed and random effect, the Hausman test is applied which indicates that the marginal effect of stated indicators is acceptable which are not correlated with the individual entities. In addition, the comparison through OLS dummies, fixed and areg (a category of linear regression) explains that again the size, LR and GDP are found to be the significant determinants of business earnings in the region of Kuwait.